MRI Diagnosis of Suspected Subcortical Heterotopia in a Mixed-Breed Dog with History of Seizures - Bishal Bhatharai; Nilsolay Kozlov; Mikhail Kashalin; Sergey Pozyabin; Mura Chora Olga; Tomas Liptak; Maria Kuricova (The Indian Veterinary Journal, 2026)
A rare case of congenital brain anomaly in a 2-year-old mixed-breed neutered female dog is presented in this study. The dog was admitted for further diagnosis because of episodic tonic-clonic generalised seizures. All blood tests and urinalysis results were unremarkable. MRI of the brain revealed an increase in volume of the frontal lobe, which was isointense to the grey matter and non-contrast enhancing and consistent with congenital subcortical heterotopia.